The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/8871602
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in Retinal and Choroidal Vascular Densities in Patients with Type 2 Diabetes Mellitus on Optical Coherence Tomography Angiography

Abstract: Purpose. In the present study, the retinal and choroidal vascular densities (VDs) in type 2 diabetes mellitus (DM) patients were analyzed using optical coherence tomography angiography (OCTA). Methods. The study included 282 eyes of 152 patients with type 2 DM (114 without retinopathy, 79 nonproliferative diabetic retinopathy (NPDR), 48 severe NPDR, and 41 proliferative diabetic retinopathy (PDR) eyes). The superficial and deep retinal vessel, choriocapillaris, and choroidal VDs were measured using a binarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The relationship between the choriocapillaris and retinal vascular plexus is another issue that is not well understood. Reviewing previous reports, most of them included patients with DR of all severities and reported that both retinal capillary plexus density and choriocapillaris density decreased along with more severe DR [9,10,[28][29][30]. According to the report of Lupidi et al [11], choriocapillaris vascular perfusion density (VPD) was negatively correlated with deep capillary plexus VPD of the retina in low-grade DR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between the choriocapillaris and retinal vascular plexus is another issue that is not well understood. Reviewing previous reports, most of them included patients with DR of all severities and reported that both retinal capillary plexus density and choriocapillaris density decreased along with more severe DR [9,10,[28][29][30]. According to the report of Lupidi et al [11], choriocapillaris vascular perfusion density (VPD) was negatively correlated with deep capillary plexus VPD of the retina in low-grade DR.…”
Section: Discussionmentioning
confidence: 99%
“…Choriocapillaris ow was found to be decreased in DR patients [9,10]. However, there are limited data on the relationship between choriocapillaris ow and other parameters, such as retinal vascular density and CTh.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…With advancements in optical coherence tomography (OCT), previous studies have demonstrated several choroidal changes associated with DR. These include changes in choroidal thickness (CTh) [ 5 , 6 , 7 , 8 ], choroidal vascular index (CVI) [ 9 , 10 , 11 , 12 ], and choriocapillaris flow. However, previous studies have reported conflicting results regarding diabetic choroidal changes.…”
Section: Introductionmentioning
confidence: 99%
“…Choriocapillaris flow is decreased in patients with DR [ 9 , 10 ]. However, there are limited data on the relationship between choriocapillaris flow and other parameters such as retinal vascular density and CTh.…”
Section: Introductionmentioning
confidence: 99%